2019
DOI: 10.1111/eea.12767
|View full text |Cite
|
Sign up to set email alerts
|

Does sharp force trauma alter blow fly attraction to, colonization of, and decomposition of vertebrate remains?

Abstract: Forensic entomologists use insect evidence to estimate the minimum postmortem interval of human remains. However, how different forms of trauma influence insect attraction to, and colonization of, the body is poorly understood. Our objective was to identify the Calliphoridae community present in the Piedmont region (Georgia, USA), and determine whether postmortem sharp force trauma (none vs. slashed vs. stabbed) altered insect attraction, colonization, and the resulting decomposition rate of stillborn pigs (Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…(2022) provided more detail on the impact of wasps on flies and carcass decomposition. In this study, carcasses were split open to simulate the scavenging activity of large vertebrates on fresh carrion, which has been shown to increase fly abundance (Meehan, Seminet‐Reneau & Quinn, 2005; Munro et al ., 2019). Although no difference in fly or wasp abundance was found between open and intact carrion in their investigation, numbers of observed wasp predation and mutilation events were higher at open carcasses, ultimately suggesting that the predatory and competitive effects of wasps can shift irrespective of wasp numbers.…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…(2022) provided more detail on the impact of wasps on flies and carcass decomposition. In this study, carcasses were split open to simulate the scavenging activity of large vertebrates on fresh carrion, which has been shown to increase fly abundance (Meehan, Seminet‐Reneau & Quinn, 2005; Munro et al ., 2019). Although no difference in fly or wasp abundance was found between open and intact carrion in their investigation, numbers of observed wasp predation and mutilation events were higher at open carcasses, ultimately suggesting that the predatory and competitive effects of wasps can shift irrespective of wasp numbers.…”
Section: Case Studiesmentioning
confidence: 99%
“…Of the biotic and abiotic factors known to modulate both the persistence of a carcass and the scavengers that use it, research has demonstrated the influence of apex (Wikenros et al ., 2013) and obligate (Ogada et al ., 2012) scavengers, and how their presence is a key indicator of a well‐functioning scavenging community (Newsome et al ., 2021). Carcass size (Moleón et al ., 2015), type (Munoz‐Lozano et al ., 2019) and condition (Selva et al ., 2005; Munro, Mondor & Lampert, 2019) can influence how long a carcass persists and the scavengers it attracts. Time of day can influence the initial use of the carcass by scavengers (Williams et al ., 2017; Carrasco‐Garcia et al ., 2018), and carcass age (days since death) can affect the quality of the tissues (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The larval phylogenetics of the Dermestidae (Coleoptera) has been studied by Kiselyova and McHugh (2006). Another study that has been helpful to forensic entomology casework is an article examining fly behavior and the alteration of attraction and colonization by sharp force trauma (Munro, Mondor, & Lampert, 2019). A unique study on the decomposition rates of crickets and millipedes in forest litter was published by Seastedt and Tate (1981).…”
Section: Forensic Entomological Literature In the South‐eastern United Statesmentioning
confidence: 99%